Bloem valley enterprise bloem valley cakes and coffees - Daini Dzulkarnain, Alyea Dania; Abdul Latif, Alyaa Nadhirah; Ahmad, Aimi Syazwani; Sakery, Nur Alyn; Khalid, Nur Diyanah (2020)
Bloem Valley Enterprise is a company that owns a cafe that will be located in SS 15 Subang Jaya, Selangor. Our café will be provided a variety of cake that offered a variety of flavours, frostings, sizes, topping and decorations such as our signature cake is Butterfly Pea Lemon Cheese Cake and we also provided coffee-based beverages only. Bloem valley will contain a comfortable seating area for ‘dine-in’ in the café while enjoying the cozy environment other than take away. However, not just that, our café also provided a delivery service can facilitate customers in terms of difficult movement in this covid-19 pandemic. Thus, as a café, Bloem Valley will have an extensive target market. People at all ages in range 20-60 especially to the people who sweet tooth lover will be included in the target market. Not just that, our affordable price of our premium and healthy ingredients of cakes and coffee also keeping the target market large. As a café, the thing that needs to be taken seriously is the product quality. Therefore, Bloem Valley will ensure the product quality through the use of healthy and quality ingredients for our customer and always make sure all the cakes are freshly baked to be serve and a focus on cleanliness. Hence, our healthy and premium ingredients are imported from New Zealand. In addition, innovations or research and development also a goal of the company which means our café will accomplish it through creating a new flavour of cakes and frostings for each festival or each month for a limited time based on customers feedback and preferred. Next, Bloem Valley serve coffee flavoured drinks as the only drink that will be sell in our café. We will make sure our cafe have fully range product from Italy espresso shot to traditional Vietnamese coffee. Our coffee will be brewed espresso-based with variety of fresh milk according to the tastes of our customers. Basically, all of our product will be freshly bake and freshly brewed for the customers. As our motto is “Smell the Happiness” that describes the smell of the freshly baked and brewed in our café. In addition, the advantages of our café are that the location for our business is strategic which is at SS15 Courtyard Subang Jaya. Our café is very accessible and easy to find in Subang, as it is in the middle of the SS15 for people to come and dine or to deliver. A company website and media social are to advertise our café. This is the best advertising to update on our promotions and our monthly specialty. Besides that, our café is located at SS15, Subang Jaya that has a large and competitive population. Basically, SS15 is a popular place of business with various businesses, especially restaurants such as fast food restaurants and westerns restaurants and cafes. Therefore, Secret Recipe, Souka Bake Shop and Vanilla Mille Crepe is the biggest competitors to our café. However, our affordable price with premium import ingredients will strive to be competitive with the industry. Costs and expenses will be calculated to provide the minimum price option to the business, preventing losses. Moreover, our business company will also conduct product price comparisons to other similar businesses in the area to find out the pricing requirements to stay competitive. Bloem Valley official opening will host a grand opening to gain customers awareness. We will be provided free samples of variety of cake and freshly brewed coffee to achieve the consumer interest and desire which will increase consumer purchases. Then we will start our business with business operation hour for 12 hours per day (10 a.m. until 10.00 p.m.), operating hour for 14 hours per day (9.00 a.m. until 11.00 p.m.) and working days for 6 days per week (Tuesday until Sunday). Moreover, we will make sure our process flow chart will be done efficiently, on time to achieve our business targets. Also, based on the activity chart, we will ensure that the service provided by our employees to serve and serve customers well, friendly, thorough and also polite in order to get positive feedback from customers. To ensure our business runs smoothly and orderly, we will have one General Manager with the most important roles, one Administrative Manager, one Finance Manager and one Operations Manager who each have a responsibility to ensure the success of this business. In addition, we will have two people as cashier, two people as barista, 3 people as baker, 4 people delivery guy and 3 people as waiter and waitress so that process flow chart and activity chart can be run efficiently.